A multiscale material-structure-hydroelasticity coupled analytical model for floating sandwich structures with hierarchical cores. (September 2021) - Fang, Hui; Zhu, Huadan; Li, Aijun; Liu, Huichao; Luo, Senlin; Liu, Yilun; Liu, Yong; Li, Huajun
Abstract: A novel material-structure-hydroelasticity coupling analytical model is proposed for marine structures, which is utilized for the calculation and optimization of a very large floating sandwich structure (VLFSS) with a hierarchical ultrahigh-performance concrete (UHPC) core in this study. For the coupling material and structure analysis, three-dimensional representative volume element and self-consistent methods are developed to reveal the physical relations between the UHPC core's macroscale mechanical properties (e.g., modulus and density) and mesoscale hierarchical characteristics (e.g., aggregate and porosity) and to obtain the corresponding parameterized formulas. For the coupling material-structure-hydroelasticity analysis, a sixth-order dynamical equation for the potential flow model of the VLFSS, in which the hierarchical core's parameters are introduced through the material-structure coupling formulas, is developed. The hydroelasticity equations containing multiscale parameters are solved, and the mechanical responses are calculated. Using this coupled multiscale method, the shear force in the representative VLFSS is optimized for a smaller amplitude, which relies on the interactivity of the hierarchical structural parameters and wave conditions. These results demonstrate the potential of the multiscale coupling methodology to achieve the physically significant optimization of a floating composite structure in ocean engineering. Highlights: A multiscale material-structure-hydroelasticity coupling analytical model is proposed. 3-D RVE, six-order dynamic motion and potential flow models are deduced and coupled. The mechanics characteristics of a very large floating sandwich structure are optimized.